Complex hydrides as thermal energy storage materials: characterisation and thermal decomposition of Na2Mg2NiH6. Issue 19 (1st May 2018) - Humphries, Terry D.; Sheppard, Drew A.; Li, Guanqiao; Rowles, Matthew R.; Paskevicius, Mark; Matsuo, Motoaki; Aguey-Zinsou, Kondo-Francois; Sofianos, M. Veronica; Orimo, Shin-ichi; Buckley, Craig E.
Abstract : The thermodynamic properties of Na2 Mg2 NiH6 have been investigated to determine feasibility as a thermal energy storage material. Abstract : Complex transition metal hydrides have been identified as being materials for multi-functional applications holding potential as thermal energy storage materials, hydrogen storage materials and optical sensors. Na2 Mg2 NiH6 (2Na + ·2Mg 2+ ·2H − ·[NiH4 ] 4− ) is one such material. In this study, the decomposition pathway and thermodynamics have been explored for the first time, revealing that at 225 °C, hydrogen desorption commences with two major decomposition steps, with maximum H2 desorption rates at 278 and 350 °C as measured by differential scanning calorimetry. The first step of decomposition results in the formation of Mg2 NiH x ( x < 0.3) and NaH, before these compounds decompose into Mg2 Ni and Na, respectively. PCI analysis of Na2 Mg2 NiH6 has determined the thermodynamics of decomposition for the first step to have a Δ H des and Δ S des of 83 kJ mol −1 H2 and 140 J K −1 mol −1 H2, respectively. Hydrogen cycling of the first step has been achieved for 10 cycles without any significant reduction in hydrogen capacity, with complete hydrogen desorption within 20 min at 395 °C. Despite the relatively high cost of Ni, the ability to effectively store hydrogen reversibly at operational temperatures of 318–568 °C should allow this material to be considered as a thermal energy storage material.